Junior High School Students’ Mathematical Problem Solving Ability on Two Variable Linear Equation System - Fauziyyah, Herlina; Putra, Harry Dwi; Anita, Ika Wahyu (IKIP Siliwangi, 2024)
The purpose of this study was to find out how well class VIII students of SMP were able to solve math problems on SPLDV material. The approach used was descriptive-qualitative, where in this study students were asked to take a problem-solving ability test with a minimum score limit of 10 and a maximum of 30 points, and the test instrument consisted of four essay questions that had been prepared. Ready. tested for high validity, high reliability, high differentiability. good, and moderate difficulty. for the research data analysis process the researcher used excel 2019, by dividing the scores obtained by students with the maximum score then multiplied by 100%. The research was conducted on 14 class VIII students of junior high schools in Bandung Regency who took part in this research. The mathematical problem-solving abilities of class VIII students are identifying elements that are known, asked, and the suitability of the elements needed in the very low category, formulating mathematical problems or formulating mathematical models in the low category, applying everyday problem-solving strategies in the high category, and Explain or interpret the results according to the initial problem in the very high category.